Researching racism: a guide book for academics and professional investigators - Quraishi, Muzammil (Sage Publications Ltd., 2015)
"Discussing the salient aspects of race and racism in contemporary society and alerting students to methodological and practical considerations of qualitative research on race and racism, Researching Racism is not only an original textbook but also a crucial guide for anyone beginning their research on racism. Based on the authors' solid and extensive background as researchers, supervisors and teachers, this book offers a clear and accessible account of an interdisciplinary and complex topic ; incorporates historical, legislative and international dimensions of race and racism ; outlines and illustrates a range of qualitative research methods ; provides case studies and engaging examples ; includes a toolkit for researchers of racism"--Page 4 of cover.